Identifying supply and demand in the Hungarian corporate loan market - Sándor Sóvágó (Magyar Nemzeti Bank, 2011)
During the recent crisis bank lending to the non-financial corporate sector declined substantially in Hungary and this slump proceeds in the aftermath of the recession as well. However it is not evident whether it is a result of the slow recovery of the real economy (the lack of credit demand), or it is caused by the balance sheet adjustment of financial intermediaries, that is tight credit supply is prevalent. In this paper we identify supply and demand in the corporate loan market in Hungary and decompose the developments of lending to supply and demand factors. Doing this a simultaneous econometric model is estimated on a panel dataset, which covers the major banks in the industry. The model takes into account the results of the Bank Lending Survey of MNB, which provides some information about lending standards and banks' willingness to lend. Our results suggest that tight supply conditions have played an important role in the decline of lending, especially after the outbreak of the crisis. At the same time, demand has been contracted as well during the recession, although it has started to recover in 2010. At the end of 2010 we may conclude that the decline in supply and demand accounted for the drop in corporate lending in a ratio of around 2/3 - 1/3, respectively.
Keywords: E44; 330; corporate lending; credit supply; bank lending survey; Kreditgeschäft; Unternehmensfinanzierung; Kreditmarkt; Angebot; Nachfrage; Ungarn